Kısmi aralıklarla akışa açılmış yatay kuyuların verimliliği - Yılmaz, A.Doğan (Fen Bilimleri Enstitüsü, 1995)
Literatürde yatay kuyuların akış performansıyla ilgili olarak bulunan çalışmaları üçe ayırmak mümkündür: (1) saha tecrübelerine dayanan, belirli bir sahada yapılanları, karşılaşılan problemleri ve bunların çözümlenmesinde izlenen yöntemleri açıklayan rapor niteliğinde çalışmalar; (2) saha davranışını genel olarak canlandırmaya çalışan nümerik simulatörler ve (3) akış performanslarını hesaplamaya yönelik analitik formüller öneren çalışmalar. Bu çalışmada ilk tip çalışmalar üzerinde durulmamıştır. Simulatörler hakkında ise sadece bir kaç örnek verilip analitik modeller üzerinde durulmuştur. Fakat bunların da sadece birkaçı yatay kuyuların seçilmiş aralıklarla tamamlanmış olması durumunu gözönüne almaktadır. Ancak bu formüller de içerdikleri karmaşık fonksiyonlar nedeniyle pek kullanışlı değildirler. Bu çalışmada, kısmi aralıklarla tamamlanmış yatay kuyuların kararlı akış koşullarındaki akış performansı için kullanışlı matematiksel bir model önerilmektedir. Bu formülün çözümünde Fourier serileri ve değişkenlerin ayranı tekniği kullanılmıştır. Modelin çalışması için akış debisinin açık aralıklara olan dağılımı konusunda bir ön bilgi veya tahmin gerekli değildir. Dikdörtgen prizma şekilli bir rezarvuarda, y doğrultusunda rezervuann tam orta noktasında olması şartıyla, x ve z doğrultularında, herhangi bir noktaya yerleştirilmiş, kısmi aralıklarla tamamlanmış bir yatay kuyunun kararlı akış koşullarındaki akış performansım hesaplamak için bir model türetilmiştir. Rezervuann alt ve üst sınırları akışa kapalıdır ve bütün yanal sınırlarda sabit basınç vardır. Yatay kuyu üzerinde N adet akışa açık aralık bulunmaktadır. Bu aralıklar kuyu üzerinde istenildiği gibi dağıtılabilir ve istenilen uzunlukta olabilirler. Kuyu boyunca her açık aralıkta birbirine eşit veya farklı büyüklükte bir zar faktörü olabileceği de gözönünde bulundurulmuştur. Ayrıca yatay kuyunun sabit ve belirli bir debide üretim yaptığı kabul edilmiştir. Model çözümünde kullanılan bilgisayar programında ayrıca her arahktan gelen akışkan miktarı da hesaplanabilmektedir. Genel olarak şu sonuçlar elde edilmiştir: yatay kuyunun verimliliği, tamamlama şekline göre, akışa açık olan intervallerin toplam uzunluğu ile artar. Ayrıca bu intervallerin kuyu üzerindeki dağılımı da verimliliği etkilemektedir. Belirtilmelidir ki; kuyunun akışa açık mtervaUerinin toplam uzunluğu ile kuyu verimliliği arasındaki ilişki doğrusal değildir.

In the early age of the technology, horizontal wells were completed as open holes or with slotted liners. There exist many models to determine the productivity of horizontal wells completed as open holes. However, in almost all the models, it is assumed that the entire drilled length of the horizontal well is productive. Production problems encountered over the years and the need for workover operations dictated the need to develop new completion techniques. Nowadays, cementing and perforating and installing external casing packers are among the well completion practises for horizontal wells. An important feature of these new completion methods is that only some segments of the entire drilled horizontal section are open to flow. Additionally, due to reservoir heterogeneity and/or non uniform formation damage, only some partitioned segments of a horizontal well completed open may produce fluid. Horizontal wells producing from only some segments of entire drilled length are refferred to as selectively-completed wells. Almost all the models presented in the literature are developed for open horizontal wells. In an attempt to predict the inflow performance of selectively completed wells, Goode and Wilkinson [9] developed an analytical model. To avoid the need for a priory knowledge or computation of the rate distribution along the well requiring the solution of a matrix, they assumed that pressure averaged uniform-flux solution is a valid representation of wellbore pressure solution. The approximation considered by Goode and Wilkinson [9] is valid if the open intervals are of equal length, symmetrically distrubuted and uniformly damaged. This study presents a new mathematical model to predict the productivity of selectively completed horizontal wells under steady state flow conditions. The model does not require a-prior knowledge of rate distribution. A rectangular parallelpiped reservoir is considered. The top and bottom of reservoir are sealed and a constant pressure exist at all the lateral boundaries. The horizontal well consists of N producing segments. No assumption is made regarding the distribution and the length of the producing segments. A variable mechanical skin distribution along the well is allowed. The well is assumed to be producing at a specified and constant rate; however, the production from each segment is obtained as a result of the computations, under steady-state conditions. The differential equation governing the flow into a horizontal well is the 3-D diffusivity equation. a2PD 1 d2PD 1 a2p, fal +kJD dyl +h2wD di *+7J-^+^^ = ° (S-D The prevailing boundary conditions for a selectively-completed well are 1. xD=0 PD(0,xD,yD) = 0 (S-2) 2. xD = xeD PD(xeD,yD,zD) = 0 (S-3) 3.yD = ywD -^=g(xd,zd) (S-4) SyD 4. yD=0 PD(xD,0,zD) = 0 (S-5) 8P 5. zD = 0 ^(xD,yD,0) = 0 (S-6) 6. zD=l -^(xD,yD,l) = 0 (S-7) 5zD DC where; G(xD,zD) = - "QlD^yD FwD^plD "^ÎD^yD rwD^-'p2D "İND^yD rwD-'-'pND 0 < xD < x, lplD XlplD < XD < XipID XiplD < XD < Xlp2D Xlp2D < XD < Xip2D Xip2D < XD *- Xlp3D Xip(N-l)D < XD < XlpND ZbwD < ZD < ZtwD ZbwD < ZD < ZtwD ZbwD < ZD < ZtwD ZbwD < ZD *. Zfc XlpND < XD < XipND > ZbwD < ZD < ZtwD XipND < XD *" XeD XlpiD - XpiD.'-'piD ' *. XipiD "~ XpiD + ^piD ' ^ ZbwD - ZwD WD ' ^ ZtwD=ZwD+WD/2 (S-8) (S-9) (S - 10) (S-ll) (S - 12) X N I i=l ZliD = l (S - 13) The dimensionless variables are defined as follows a.27ddl[Pe-P(x,v,Z)] (S_14) (S-15) (S - 16) (S - 17) (S-18) (S - 19) (S - 20) (S - 21) (S - 22) (S - 23) (S - 24) qJD=qi/qt (S-25) kŞD=kx/ky (S -26) XI h2 k wD T2 pt z (S - 27) The boundary- value-problem described by Eq.(S - 1) through (S - 13) can be solved using the seperation of variables technique. The solution is derived for each segment. To approximate the infinite conductivity wellbore condition, pressure averaging on each open segment is applied. The final wellbore solution for jth interval is obtained as follows: 2wDkyoXeD n. qjD j iwDJ^pjD i=l m=l J-'piD m ^m SJD "2_ T Z-f/LlT ~,2 £ ""?".ymO'"'',-xmj-,'',"xmi 4V Y N CO CO HJŞrDAeD yyy qjp ^^wD WDLpjD i=l m=l n=l LpiD m2n2 (^ + X,2n ) R.T"RT;RT;R: 1/2 ynm xmj wm zn (S - 28) where; Rymo = tanh(kyD^mywD) (S - 29) Rynm = ^h kyDfe2m+^)1/2ywD (S - 30) Rxmj = {cos[m7i(xpP + LpP /2)/xeD]-cos[m7c(xpP -LpP /2)/xeD]} (S - 31) Rm = {sin[n7c(zwD +wD/2)]-sin[nrc(zwD -wD/2)]} (S - 32) Eq.(S - 28) can be rewritten as; sjD - / jQiD^ii (S - 33) xn If i*j 2w k x n «o i T _ ^wpSp*ep VV- -- R R R.J _2 t t Z-(Z-(_,2c ^ymO^xmj^xmi ;l 1wDJ-'pjD-L'piD i=l m=l m Sm + T'KyljX^ N oo oo WV- tcV^L^L ^^^ wD D pjD piD i=l m=l t?mvfe+x2nr R^R-jR^Rz (S -34.a) If i = j Oty V Y N CO 1 T _ Z'WDKyDX-eP y^y i p R R ij 2 t t 7,7, 2e ymO xmj xmi 71 ^P^piP^piP i=l m=l m Sm + ^^yDXeD N oo oo ^4rwP WDLpjDLpiD i=] m=1 n=1 m2fl2 (^ + ^J R RT,;RT,R, 1/2 ymn xmj xmi zn + - >jD 'pjP (S -34.b) In the second step, a uniform pressure along the entire length of the horizontal well is imposed and the pressure of each producing interval is equated to the wellbore pressure PwD. Thus writing Eq.(S - 33) for each producing segment and using the total flow rate equation a matrix is obtained with wellbore pressure and rate distribution as unknowns. 1 -T ?Mi L21 v31 M2 -T -T l22 32 _T _T _T -Ml -"-Ol -A-J M3 M4 23 l33 -T -T l24 34 1 _T _T *-3N (S - 35) xm the solution of matrix problem given in Eq.(S - 35) yield the unknown wellbore pressure and rate distibution. A computer code is written to compute Eq.(S - 35). The solution presented here was compared to open horizontal well solutions given by Joshi [1,2] and Özkan [7]. Good agreement was established between the results from the models in the literature and the results from Eq.(S - 35). A second comparison test considering a selectively completed well is conducted between our model and the model presented by Goode and Wilkinson [9]. Reasonable agreement is observed between the models.
Productivity of selectively completed horizontal wells
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1995
Keywords: Petrol ve Doğal Gaz Mühendisliği; Kuyular; Petroleum and Natural Gas Engineering; Wells